Unlicensed capitalism, Greek style illegal markets and 'organised crime' in Greece - Antonopoulos, Georgios ca. 20./21. Jh; Papanicolaou, Georgios 1973- (Wolf Legal Publishers, 2014)
"Manifestations of what mainstream criminology currently identifies as 'organised crime' have long existed in Greece and in some respects exhibit deep roots in the country's economic and cultural history. The term as such, 'organised crime', was only brought to currency in the 1990s by the media in the country. Curiously this was not a development preceded or followed by extensive and reliable research. From a criminological viewpoint, very little is known on 'organised crime' in Greece either in general or on specific types of 'organised crime'. As case studies and official accounts are few and far apart, the widespread use of the term in public debates bears more the unmistakable marks of truthiness than factuality. The purpose of this book, which comprises a number of previously published case studies, is precisely to challenge the taken-for-granted, mainstream accounts featuring a certain exceptionalist notion of 'organised crime'; that 'organised crime' is invariably associated with certain groups and milieus, a dark and obscure underworld radically separated from an orderly and lawful upperworld. The five case studies included in this book directly challenge this view across a range of illegal markets : the cigarette black market, the car theft and trafficking business, the Ecstasy market, human smuggling and trafficking, and the counterfeit CD/DVD market. The concluding chapter provides a synthesis of the empirical evidence presented and attempts to connect research findings with a series of questions of both theory and policy."--Back cover
Keywords: Organized crime / Greece; Organized crime; Organisiertes Verbrechen; Greece; Griechenland